Translation and Validation of Oral Health-Related Early Childhood Quality of Life Tool for Nepalese Preschool Children - Upadhyay, S.; Mathur, V. P.; Dhillon, J. K.; Poudyal, S. (Kathmandu University Medical Journal, 2021)
Background Early childhood caries (ECC) in preschool children debilitate their quality of life affecting oral function, appearance and social well-being. A tool for measuring oral health-related quality of life for preschoolers may help in making clinical decisions and assist policy makers in planning and management of health programs in the country. Objective To translate oral health-related early childhood quality of life (OH-ECQoL) tool into Nepali language and test its validity and reliability. Method OH-ECQoL was translated into Nepali language by two Nepalese professional translators which was back translated by professional English translator. This was sent to three independent advisors to see the appropriateness of translation. Pilot testing was done in 20 parents and questionnaire was finalized after needed corrections. Final version was introduced to the 118 parents of children aged 24- 71 months. Caries status was recorded for all children participating in the study. Concurrent, construct, discriminant validity and internal consistency reliability, test -retest reliability were evaluated. Result OH-ECQoL scores and perception of parents for general and oral health of their children was significant (at 0.01 level). There was significant difference in OH-ECQoL scores between no ECC and severe ECC groups and moderate and severe ECC groups (at 0.05 level). There was also a significant correlation between child impact section and family impact section (at 0.01 level). Cronbach’s alpha was 0.891 demonstrating good internal consistency. Intra class coefficient was 0.963 suggesting excellent test-retest reliability. Ninety-one (77.1%) children had severe ECC and 40(33.9%) parents were from upper middle class. Conclusion The Nepali version of OH-ECQoL is a valid and reliable tool for assessing the oral health-related early childhood quality of life in children of Nepal.